2009
DOI: 10.1002/cncr.24168
|View full text |Cite
|
Sign up to set email alerts
|

Race impacts outcome in stage III/IV squamous cell carcinomas of the head and neck after concurrent chemoradiation therapy

Abstract: BACKGROUND:The purpose of this study was to determine the impact of race on outcome in patients with stage III/IV squamous cell carcinoma of the head and neck (SCCHN) who have completed concurrent chemoradiotherapy.METHODS:The authors performed a retrospective analysis of 202 patients with stage III/IV SCCHN who were treated at the University of Maryland. Patients received daily radiation to a total dose of 70.2 Gray (Gy) (1.8 Gy/day), concurrently with weekly carboplatin (area under the curve [AUC] = 2) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 18 publications
3
29
1
Order By: Relevance
“…From these patients, we selected a homogeneous cohort of white and black patients treated curatively with concurrent chemoradiotherapy for previously untreated SCCHN with no evidence of distant metastases. The strongest findings of our previously published and related retrospective analysis [based on a shorter median follow-up (versus the present analysis) of 33 months] involved disease-free survival (10). For the retrospective analysis presented here, we updated survival data with a focus on OS in all and oropharyngeal SCCHN patients and how OS may have differed by race.…”
Section: Methodscontrasting
confidence: 50%
See 1 more Smart Citation
“…From these patients, we selected a homogeneous cohort of white and black patients treated curatively with concurrent chemoradiotherapy for previously untreated SCCHN with no evidence of distant metastases. The strongest findings of our previously published and related retrospective analysis [based on a shorter median follow-up (versus the present analysis) of 33 months] involved disease-free survival (10). For the retrospective analysis presented here, we updated survival data with a focus on OS in all and oropharyngeal SCCHN patients and how OS may have differed by race.…”
Section: Methodscontrasting
confidence: 50%
“…Intensity of treatment was similar for the two groups and did not account for the differences in survival. In a previously reported retrospective analysis (10), we showed that disease-free survival was significantly greater in white than in black SCCHN patients who were treated with chemoradiation; the greatest black-white difference occurred in the oropharyngeal subgroup. We also recently analyzed race-related outcomes in two Radiation Therapy Oncology Group studies in head and neck cancer, finding in both studies that blacks had a significantly poorer outcome compared with whites, despite receiving identical treatment (11).…”
mentioning
confidence: 61%
“…Differences in socioeconomic status, biologic/genetic variation, and disproportionate exposure to alcohol and tobacco products are implicated as potential contributors to the excess incidence of HNC among African American patients [8,10,20,21]. Increasing oral health education has been suggested as a preventative approach to help reduce the environmental risks that African Americans are exposed to [22].…”
Section: Discussionmentioning
confidence: 97%
“…A worse outcome has been reported for African-American patients with breast cancer, 15 squamous cell cancers of the anus 16 and head and neck, 17 endometrial cancer, 18 and even for pediatric patients undergoing treatment for Hodgkin’s lymphoma. 19 In their analysis of 19,457 adult cancer patients treated on Southwest Oncology Group (SWOG) phase III trials, Albain and colleagues determined that African-American patients with early-stage premenopausal and postmenopausal breast cancer, advanced-stage ovarian cancer, and advanced-stage prostate cancer had increased mortality.…”
Section: Discussionmentioning
confidence: 99%